Elemental Content of Three Plant Species Growing on Abandoned Fly Ash Landfill - Chaudhary, D. R.; Ghosh, Arup; Chikara, J.; Patolia, J. S. (Indian Forester, 2009)
Differences in foliage tissue concentration of elements were assessed for Prosopis juliflora, Calotropis gigantia and Ipomoea fistulosa growing on abandoned fly ash and a control soil (Mixed, hyperthermic Typic Ustochrepts). In general, plants from the fly ash exhibited reduced concentrations of N, K, Ca, Mg, S and Mn while elevated trace element concentration in comparison to the control. However, plants growing on fly ash were well supplied with phosphorus nutrition. One of the most striking differences in the trace elemental concentrations among the fly ash and control plants was observed for Mn, as the control plants exhibiting concentrations orders of magnitude greater than the fly ash. Based on elemental concentration of plants grown on soil and fly ash, Prosopis showed less difference in elemental concentration between both locations compared to other trees and can be used for rehabilitation of fly ash landfills with forestry point of view.